Обгрунтування стратегії розвитку підприємства в умовах кризи - Павленко, Олена Сергіївна; Pavlenko, Оlena; Кобець, Є. А.; Kobets, Ye.; Корольов, Д. Д.; Korolyov, D. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
Стратегічний план антикризового управління стосується серії заздалегідь визначених дій і рішень, прийня тих підприємством для ефективного управління кризою. План окреслює кроки, які вживає організація, щоб запобігтикризі, підготуватися до неї, реагувати на неї та вийти з неї. Стратегічний план має бути розроблений до виникнення будьякої кризи та має бути достатньо гнучким, щоб адаптуватися до мінливих обставин кризи. План має бути чітко доведений до відома всіх зацікавлених сторін, і кожен в організації повинен усвідомлювати свою роль у реалізації плану. Неможливо переоцінити важливість стратегічного плану управління кризою. Добре розроблений план може допомогти компаніям мінімізувати вплив кризи, захистити репутацію компанії та зберегти довіру зацікавлених сторін. І навпаки, відсутність планування може призвести до плутанини, нерішучості та повільних реакцій, що може посилити кризу та завдати довгострокової шкоди. A strategic crisis management plan refers to a series of predetermined actions and decisions taken by an enterprise for effective crisis management. The plan outlines the steps the organization takes to prevent, prepare for, respond to, and recover from a crisis. A strategic plan should be developed before any crisis occurs and should be flexible enough to adapt to the changing circumstances of the crisis. The plan must be clearly communicated to all stakeholders, and everyone in the organization must be aware of their role in implementing the plan. The importance of a strategic crisis management plan cannot be overstated. A well designed plan can help companies minimize the impact of a crisis, protect the company's reputation, and maintain the trust of stakeholders. Conversely, alack of planning can lead to confusion, indecision and slow responses, which can exacerbate a crisis and cause longtermdamage. A strategic crisis management plan can help ensure the financial viability of companies, increasing their ability to adapt to market changes and be competitive. Effective communication is helpful in having a strategic crisis management plan. During a crisis, it is critical to have effective and informed communication to let all parties involved know that things are going wrong. The comprehensive crisis management plan includes protocols for communication with employees, customers, suppliers and other stakeholders, as well as a designated secretary to answer questions from the media. By creating a plan, companies can reduce ambiguity and error, maintain transparency, and build trust with their stakeholders. The strategic plan of anticrisis management should contain a comprehensive approach to enterprisemanagement.This includes taking into account certain attributes of the business, such as its size, industry and market structure. In addition, the plan must be regularly evaluated and revised to maintain its relevance and effectiveness. By taking astrategic approach to crisis management, businesses can strengthen their defenses against potential threats and contribute to long-term viability and success.
Justification of the development strategy of the enterprise in crisis conditions
Keywords: стратегічне управління; strategic management; розвиток підприємства; enterprise development; криза; crisis; антикризове управління; anti-crisis management; SWOT; SWOT; PESTEL; PESTEL